Ovarian Cancer - Lele, Shashikant (Exon Publications, 2022)
Ovarian cancer is a leading cause of gynecological cancer-related deaths in women worldwide. Due to the lack of specific signs and symptoms at the early stages of the disease, ovarian cancer is usually diagnosed late, and peritoneal and distant metastases are common at diagnosis. While there is no curative treatment for advanced ovarian cancer, our understanding of the disease has significantly advanced in the past decade. Ovarian cancer is a highly heterogeneous disease. A key feature of advanced ovarian cancer is malignant ascites, the pathological accumulation of fluid in the peritoneal cavity. Inflammation and inflammasomes play a key role in this process. In this book, an international team of researchers and clinicians provide an up-to-date information on aspects of heterogeneity, pathological mechanisms, and treatment strategies. The heterogeneity of ovarian cancers is covered in the chapter on subtypes of ovarian cancer. The pathological mechanisms with emphasis on malignant ascites and inflammasomes, and how they contribute to tumor progression and chemoresistance are comprehensively presented in three chapters. The last three chapters focus on current and future treatment strategies with emphasis on the real-life challenges faced in the clinics by gyneco-oncologists in daily practice in the management of recurrent high grade serous ovarian cancer, theranostics, and immunotherapy. The chapters of this book are topical. This book will be valuable to healthcare professionals caring for individuals with ovarian cancer and researchers involved in ovarian cancer.